THE EFFECT OF GIVING AMBON BANANA (MUSA PARADISIACA.L) TO EMESIS OF GRAVIDARUM IN PREGNANT WOMEN AT SIDOMULYO HEALTH CENTER OFPEKANBARU IN 2019 - Molisa, Yufa; ., Lailiyana; Laila, Ani (Poltekkes Kemenkes Riau Under Health Ministry Republik Indonesia, 2020)
Abstract Emesis Gravidarum is a common symptom in pregnancy and occurs in 50-60%of pregnant women. In addition to consuming drugs to treat nausea andvomiting, mothers can try the recommended fruits such as bananas which canovercome Emesis Gravidarum. In bananas it contains Vitamin B which issoluble in water and helps increase the development of central nervous systemcells in the fetus. A preliminary survey conducted at the Sidomulyo InpatientHealth Center in Pekanbaru City showed that 8 out of 10 pregnant womenexperience Emesis Gravidarum so that it can cause discomfort for pregnantwomen. The purpose of this study was to effect of ambon banana on EmesisGravidarum in pregnant women at Sidomulyo Inpatient Health Center,Pekanbaru City in 2019. This type of research is a pre-experiment with onegroup pre-post test design. This research was conducted from March to June2019. The population in this study were all pregnant women who experiencedEmesis Gravidarum with a sample of 19 people taken by accidental samplingtechnique. The results showed that the average score of nausea vomiting withmothers Emesis Gravidarum before given ambon banana was 10,21(SD=2,175) and after being given ambon banana was 7,21 (SD=2,200). Theresult of the Wilcoxon test statistical test showed that there was an effect ofgiving ambon banana to Emesis Gravidarum in pregnant women with (p-value0,000). It is recommended for midwives to provide education about ambonbanana as one of the nutrients from natural ingredients to reduce EmesisGravidarum during pregnancy.